Ab Initio Prediction of Tunneling Relaxation Times and Effective Demagnetization Barriers in Kramers Lanthanide Single-Molecule Magnets - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2018)
Single-molecule magnets (SMMs) are promising candidates for molecule-based quantum information devices. Their main limitation is their cryogenic operative temperature. To achieve devices performing at higher temperatures, demagnetization mechanisms must be suppressed by chemical tuning. Electronic structure calculations can provide useful information to rationalize SMM behavior, but they do not provide a direct prediction for the key experimental parameters describing magnetic relaxation (i.e., tunneling relaxation time (τQT) and effective demagnetization barrier (Ueff)). In this Letter, a first-principles model is proposed to predict τQT and Ueff for mononuclear, half-integer spin SMMs, allowing direct comparison with experiment. Model accuracy was assessed against experimental data for 18 mononuclear LnIII complexes (15 DyIII and 3 ErIII) and applied to 3 of the current best-performing SMMs, correctly predicting nontrivial relaxation pathways. The model shows that the combination of single-ion anisotropy and spin-spin dipolar coupling can account for the major part of tunneling demagnetization for the studied systems. © 2018 American Chemical Society.